(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
The negative influence of fossil fuels and the limited supply of fossil fuels to encourage researchers are looking for alternative fuels to renewable energy, namely coconut oil and jatropha oil. The purpose of this study was to determine the ratio of the combustion flame spray on burning long, wide combustion and combustion stage by studying the experimental results of burning coconut oil and jatropha oil, camera recording video at 420 fps in the spray nozzle tester with 1900 psi pressure. The results of the comparative analysis, combustion spray seed oil kapok better than castor oil, this is indicated in the data there is a difference of 20.73% the length of the combustion spray maximum of coconut oil than jatropha oil, the burning of coconut oil reach flames maximum is 164 cm and oils a distance of 130 cm, for width measurement obtained difference of 23.60% a wide range of flame spray a maximum of coconut oil than jatropha oil, coconut oil range of flame spray a maximum of 33.7 cm and jatropha oil is 28.8 cm, and the results of the analysis phase of burning, coconut oil occurs twice burning while the jatropha oil are three stages of combustion.